Defining and operationalizing ‘nature-positive’ — a question of power - Stenseke, Marie; Olsson, Johanna Alkan; Arvidsson, Susanne; Droste, Nils ; 0000-0003-4357-9115; Elliot, Viktor; Gipperth, Lena; Smith, Henrik G. ; 0000-0002-2289-889X (Current Opinion in Environmental Sustainability, 2025)
This paper examines how the concept ‘nature-positive’ as a means to enhance biodiversity is defined and used, viewed through the lens of power. Building on a three-dimensional conceptualization of power, we elaborate on i) how ‘nature-positive’ enters and remains on business and policy agendas, ii) different interpretations from both ecological and business perspectives, and iii) the governance of its implementation. Our findings reveal divergent positions, where some argue for a clear and operational definition that makes the concept practical for business and enforceable in legal frameworks. Others adopt a more critical standpoint, viewing it as a boundary object that facilitates processes encouraging positive actions. At the same time, yet other voices regard it as a distraction from addressing the structural drivers of biodiversity loss. We conclude that, from a normative standpoint, an open and ideally balanced debate would empower multiple voices and interpretations. Reflecting on who stands to benefit from different operationalizations is important from a justice perspective. For ‘nature-positive’ to serve as a driver of transformative change, it must be underpinned by a robust toolkit capable of addressing the complexity of biodiversity and its multiple values.
Publisher Copyright: © 2025 The Author(s)